Identification of The Chemical Compound from Ethyl Acetate and Ethanol Fraction of Banana Peel Extract (Musa Acuminata Colla) - Hadi Barru Hakam Fajar, Siddiq; Denok Risky Ayu , Paramita; Agnis Pondineka Ria, Aditama; Rosida, Rosida (Indonesian Chimica Letters, 2025)
Bananas are broadly utilized as an alternative nourishment, whereas banana peels, as squander, are right now as it were utilized as creature nourish added additives. Banana peel contains flavonoids, saponins, glycosides, alkaloids, tannins, and catechins. Flavonoids are phenolic compounds (phenolic hydroxyl) that can act as cancer prevention agents and are by and large found in plants. This inquiry will recognize the chemical compounds of the ethyl acetic acid derivation division and the ethanol division of the banana peel extract (Musa acuminata Colla). This sort of investigation is a test research facility investigation with a Quasi-Experimental Plan investigate plan. In this consider, two sorts of fractionation were performed on the banana peel extract, specifically ethanol fractionation and ethyl acetate extraction fractionation. Besides, the formation of the fractionation was analyzed utilizing the LC-HRMS strategy. The comes about appears that the ethanol division of the banana peel extract contained different chemical compounds, including 4-methoxycinnamaldehyde, choline, and catechin. Within the ethyl acetic acid derivation division, the banana peel extract contained a few chemical compounds, including 5-hydroxymethyl-2-furaldehyde, diisobutylphthalate, and pyrogallol. These compounds appear in a huge region within the scope of HPLC-MS investigation.